DOES SPIRITUALITY GIVE AN IMPACT TO WELL-BEING OF ENTREPRENEUR? - Wuri, Wulan Wiyat; Andriani, Prima; Utama, Radikal Yudha (Jurnal Ekonomi & Studi Pembangunan, 2019)
Spirituality directs individuals to be more supportive in various work activities, especially in entrepreneurship context. This study examine the effect of subjective spirituality on entrepreneurs’ well-being by using data from the Indonesian Family Life Survey (IFLS) from 2007 to 2014.  We dissect the analysis into three groups that are self-employed, business owner or employer, and employee. The result stated that spirituality does matter only for those who run the business as self-employed in terms of generating income, although they tend to have lower levels of well-being rather than those who run businesses as business owners and those who work as employees within company. We found no significant evidence that spirituality affects the well-being of business owners, on the other hand this group has the highest level of well-being. The contributions of the study are explained further in this paper